2009
DOI: 10.1186/1423-0127-16-95
|View full text |Cite
|
Sign up to set email alerts
|

CHD5 is down-regulated through promoter hypermethylation in gastric cancer

Abstract: BackgroundNonhistone chromosomal proteins in concert with histones play important roles in the replication and repair of DNA and in the regulation of gene expression. The deregulation of these proteins can contribute to the development of a variety of diseases such as cancer. As a nonhistone chromosomal protein, chromodomain helicase DNA binding protein 5 (CHD5) has recently been identified as the product of a novel tumor suppressor gene (TSG), promoting the transcription of p19ink4a and p16arf. The inactivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
112
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 24 publications
5
112
0
Order By: Relevance
“…The downregulation of AnxA6 in GC cells is a result of the methylation of its promoter region, as indicated by the fact that a typical CpG island (CGI) in the promoter region of the ANXA6 gene was observed to be methylated in a number of GC cell lines. Furthermore, the expression of AnxA6 may be restored following demethylation treatment (30). The methylation of AnxA6 in GC cells was closely associated with yin yang 1 (YY1), a transcription factor involved in the initiation and maintenance of DNA methylation (30).…”
Section: Anxa6 Is Downregulated Through Promoter Methylation In Gastrmentioning
confidence: 99%
See 2 more Smart Citations
“…The downregulation of AnxA6 in GC cells is a result of the methylation of its promoter region, as indicated by the fact that a typical CpG island (CGI) in the promoter region of the ANXA6 gene was observed to be methylated in a number of GC cell lines. Furthermore, the expression of AnxA6 may be restored following demethylation treatment (30). The methylation of AnxA6 in GC cells was closely associated with yin yang 1 (YY1), a transcription factor involved in the initiation and maintenance of DNA methylation (30).…”
Section: Anxa6 Is Downregulated Through Promoter Methylation In Gastrmentioning
confidence: 99%
“…A study by Wang et al (30) indicated that the mRNA levels of AnxA6 were downregulated in GC cell lines and primary gastric carcinoma tissues compared with stomach epithelium cells and normal paracancerous tissues, respectively. Restored expression of AnxA6 in MKN28 cells inhibited their growth and clonogenic ability through inhibiting Ras/MAPK activity.…”
Section: Anxa6 Is Downregulated Through Promoter Methylation In Gastrmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, identification of novel TSGs inactivated by promoter methylation will be of great importance in understanding the progression of gastric cancer, and could be utilized as biomarkers for the early detection of cancer (7)(8)(9). We and others have found that zinc finger of the cerebellum (ZIC1), fructose-1, 6-bisphosphatase-1 (FBP1), chromodomain helicase DNA binding protein 5 (CHD5), protocadherin 10, and Klotho genes were silenced epigenetically in gastric cancer (10)(11)(12)(13)(14). In the current study, we demonstrate HoxD10 as another important TSGs which undergoes epigenetic modification.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it also has been reported that aberrant CHD5 promoter methylation was detected in gastric, colorectal, ovarian and lung cancer (20)(21)(22)(23). However, to the best of our knowledge, the role of CHD5 promoter methylation status in breast cancer has not been evaluated.…”
Section: Discussionmentioning
confidence: 89%